Pengaruh Toxic Parents Terhadap Kondisi Psikis dan Motivasi Belajar Santri di Pondok Pesantren - Ramadani, Asyi syifa; Ningsih Fadhilah (JURNAL PSIKOLOGI MANDALA, 2024)
The purpose of this study was to explore the impact of toxic parental behavior on the psychological condition and enthusiasm for learning of students in Islamic Boarding Schools. The phenomenon of toxic parents is a crucial issue in the process of character formation and mental health of adolescents, especially when children grow up in families with minimal emotional support. The method used in this study is a qualitative method with a case study method on a student who experienced verbal and physical violence, and faced family conflicts such as infidelity and domestic violence. Data collection techniques include in-depth interviews, direct observation, and psychological instruments Depression Anxiety Stress Scales (DASS-21). The findings show that emotional and physical violence have a real influence on the emergence of psychological disorders such as mild depression, moderate anxiety, and severe stress in the research subjects. These disorders also have an impact on decreased interest in learning and difficulty concentrating when participating in academic activities. This study emphasizes the importance of psychosocial support in Islamic boarding schools,such as counseling services, trauma management training, and strengthening the role of educators as emotional companions. Collaboration between Islamic boarding schools,families, and professionals in the field of psychology is very urgent in order to create asafe, supportive, and caring learning environment for the mental condition of students. Keywords: toxic parents, santri psychology, learning motivation, emotional violence,Islamic boarding schools.